A near-infrared and colorimetric fluorescent probe for palladium detection and bioimaging. (February 2017) - Su, Wei; Gu, Biao; Hu, Xiaojun; Duan, Xiaoli; Zhang, Youyu; Li, Haitao; Yao, Shouzhuo
Abstract: A near-infrared (NIR) and colorimetric fluorescent probe was developed for palladium species via a palladium catalyzed deallylation reaction. In this probe, 6-hydroxy-2, 3-dihydro-xanthene-indolium (CyH ) was acted as the signal unit and an allyl carbonate group was acted as the recognition unit. This non-fluorescent probe molecule can release the relevant fluorophore after interaction with palladium. The sensing mechanism was investigated by optical spectrum and NMR spectra. The probe can be used for "naked-eye" detection of palladium, and exhibited high selectivity to palladium over various other metal ions. Furthermore, the probe can be applied to imaging intracellular palladium ions in living HeLa cells, indicating its great potential for in vivo bioanalytical applications. Graphical abstract: Highlights: A novel near-infrared fluorescent probe for palladium has been developed. The probe showed high sensitivity and selectivity toward palladium. The probe can be applied to the visual detection for palladium by "naked-eye". The probe was used for sensing palladium in living cells.